Reflections From the Intersection of Health Professions Education and Clinical Practice: The State of the Science of Interprofessional Education and Collaborative Practice. (June 2016) - Lutfiyya, M. Nawal; Brandt, Barbara F.; Cerra, Frank
Abstract : This informed reflection, from the intersection of health professions education and clinical practice, takes stock of the state of the field of interprofessional education (IPE) and collaborative practice (CP) (together IPECP) by answering the following three questions: (1) As a field of study, where is IPECP? (2) As a research enterprise, what are the current analytical gaps? (3) Scientifically, what needs to be done going forward? While IPE and CP, as well as IPECP, have been areas of scholarly inquiry for nearly 50 years, they have collectively and individually had a limited sphere of influence. Analytical gaps identified include little research dealing with big picture health-related outcomes; mixed results on the effectiveness of health care teams; increasing recognition that additional IPECP competencies might be needed; a gap between the identification and application of educational best practices; and the need for sound, reliable, and validated tools for measuring IPECP. The authors outline the work of the National Center for Interprofessional Practice and Education at the University of Minnesota, which is focused on filling the identified analytical gaps by way of strategic actions organized around three domains—(1) developing an IPECP research agenda, (2) nurturing IPECP intervention research grounded in comparative effectiveness research study designs and the assumptions of critical realism, and (3) the creation of a sound informatics platform. The authors argue that filling these gaps is important because if the effectiveness of IPE on CP and of CP on health outcomes is ever to be ascertained, generalizable findings are paramount.